Optimalisasi Saluran Distribusi dalam Pemasaran Jamur Tiram di UMKM Kabupaten Simalungun - Junaidi Junaidi; Debora Silvia Hutagalung; Roy Sahputra Saragih; Merry Merry (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This study aims to determine the constraints faced by farmers of oyster mushroom cultivators as well as manufacturers of processed oyster mushrooms products belonging to the Group of Women Farmers (KWT) UMKM Simalungun. Respondents intentionally set, including the chairman and members of the (KWT) UMKM Simalungun Group, PPL, and regular consumers from Pradnyagama autism children Foundation. Internal and external factors are identified and analyzed by SWOT analysis to determine some alternative strategies accordingly. Furthermore, alternative strategies are analyzed by QSPM to determine strategic priorities. The results of the research show that based on internal analysis, the oyster mushroom processing business of UMKM Kabupaten Simalungun is on the average position in the harness strengths and weaknesses. The main strength of UMKM Kabupaten Simalungun is in the product variation. The main weakness of UMKM Kabupaten Simalungun is the selling price of the product. Based on the analysis of the external environment, the oyster mushroom processing business of UMKM Kabupaten Simalungun is taking advantage of the opportunities to overcome the threats faced by UMKM Kabupaten Simalungun. The main opportunity for UMKM Kabupaten Simalungun is rising customer demand. The main threat of UMKM Kabupaten Simalungun is rising production costs. SWOT Analysis discover 6 alternative strategies namely: open opportunities for cooperation with other parties associated with the distribution of products, increased sales promotion or dissemination of products information, improving the appearance of products through improved packaging, looking for market information by using information technology, trying to maintain product quality and increase efficiency and effectiveness in marketing the product